Patient references in the 2005 and 2015 CanMEDS frameworks - Adam, Holly L; Eady, Kaylee; Moreau , Katherine A (Canadian Medical Education Journal, 2023)
Background: Patient involvement in postgraduate medical education (PGME) can help residents improve their communication, professionalism, and collaboration. The CanMEDS Framework defines such competencies for physicians and informs teaching and assessment activities in PGME. However, it is unclear how patients are referenced in the CanMEDS Framework and if these references encourage the active involvement of patients in PGME. To inform how patients are referenced in the revisions of the CanMEDS Framework, scheduled for publication in 2025, our aim was to determine how patients are referenced in each the 2005 and 2015 CanMEDS Frameworks. Methods: We used document analysis to examine how the term ‘patient(s)’ is referenced in the 2005 and 2015 CanMEDS Frameworks. Results: Several 2005 and 2015 CanMEDS Roles include patients in the descriptions but do not reference them in the competencies. Others do not reference patients in the descriptions or competencies, potentially detracting from the importance of involving patients. As it stands, the 2015 Health Advocate is the only Role that describes and references patients working with physicians as partners in care, facilitating potential opportunities for patient involvement in PGME. Conclusion: There are inconsistencies in how patients are described and referenced as potential partners in PGME throughout past and present CanMEDS Frameworks. Understanding these inconsistencies can inform the revision of CanMEDS that is scheduled for publication in 2025.